2011
DOI: 10.1080/08870440903225892
|View full text |Cite
|
Sign up to set email alerts
|

Negative perfectionism increases the risk of fatigue following a period of stress

Abstract: Cognitive-behavioural models of excessive fatigue suggest that people who believe that failure to meet high standards indicates unacceptability to others (a form of 'negative perfectionism') are at risk of fatigue after a period of illness or stress. The present study investigates this using a prospective design and possible mediating factors between such beliefs and fatigue were also investigated. Undergraduate students completed questionnaires at the beginning of the academic year (time 1; n = 436) and again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 43 publications
5
30
0
1
Order By: Relevance
“…However, our lagged analyses showed that stress and fatigue also predicted each other across time independent of momentary associations. So far, only a small number of longitudinal studies have tested the stress-fatigue relationship, generally showing that stress predicted fatigue (Akerstedt et al, 2014;Dahlgren et al, 2005;Dittner et al, 2011;Kato et al, 2006). Our results are in line with these earlier studies and extend the existing data by suggesting that fatigue predicted stress both on a momentary basis as well as prospectively within days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our lagged analyses showed that stress and fatigue also predicted each other across time independent of momentary associations. So far, only a small number of longitudinal studies have tested the stress-fatigue relationship, generally showing that stress predicted fatigue (Akerstedt et al, 2014;Dahlgren et al, 2005;Dittner et al, 2011;Kato et al, 2006). Our results are in line with these earlier studies and extend the existing data by suggesting that fatigue predicted stress both on a momentary basis as well as prospectively within days.…”
Section: Discussionsupporting
confidence: 93%
“…There is a relative scarcity of studies examining the relationship between stress and fatigue as individuals engage in their daily life routines in their own environments. One notable exception is a study by Dittner, Rimes, and Thorpe (2011), in which the authors showed that fatigue levels in first-year college students were significantly higher following a period of academic stress than at the beginning of the academic year. However, in this study, perceived stress was only measured at the second time point.…”
Section: Introductionmentioning
confidence: 90%
“…Specifically, individuals higher in perfectionism who also experienced a high number of events that threatened self-esteem showed elevated psychosomatic symptoms. The results of these studies accord with findings indicating that perfectionists exposed to stress tend to have health-related reactions (Dittner, Rimes, & Thorpe, 2011) and the experience of daily hassles seems to underscore the link between trait perfectionism and headaches (Bottos & Dewey, 2004).…”
Section: Chapter 7 (Molnar Et Al) -14supporting
confidence: 81%
“…For example, numerous traits such as alexithymia, Type D, cynical hostility, perfectionism and self-control have been found to moderate the effects of stress and/or have direct effects on various health-related outcomes (e.g., Boals, vanDellen, & Banks, 2011;Dittner, Rimes, & Thorpe, 2011;Howard & Hughes, 2012;O'Connor & Ashley, 2008;Ruthig, Hanson, Pedersen, Weber, & Chipperfield, 2011;Williams, O'Connor, Grubb, & O'Carroll, 2011). In the current issue, of particular note is the study by Howard and Hughes (2012) which explores the validity of Type D personality construct in the general population.…”
Section: Challenge #3: Need To Incorporate Personality and Lifespan Amentioning
confidence: 99%